Quality improvement of the preoperative bathing practice before caesarean section in the Obstetrics-Gynaecology Unit of Cibitoke Hospital, North-Western Burundi - Ciza, Roger (My University, 2021)
Surgical site infections (SSIs) are an important public health issue in both high (HIC) and low and middle-income country (LMIC) settings. Having a caesarean section (C-section) may be associated with the risk of SSI. Preoperative bathing before C-section is recommended as a cost effective intervention to prevent SSI. However, little is known of how health professionals in LMIC implement or improve this practice. This study aimed to improve the practice of preoperative bathing practices before C-section by using the model for improvement (MFI) in the Obstetrics-Gynaecology (OBGYN) Unit of Cibitoke hospital, Burundi which had previously reported SSI. Methods A quality improvement team (QIT) was assembled and trained on the use of MFI by the principal investigator (PI). A quasi-experimental study design based on the principles of MFI was conducted. The quasi-experimental study comprised pre-intervention (baseline), intervention and post-intervention (endline) phases to assess the preoperative bathing practices, identify factors leading to poor practices, identify test change ideas and evaluate the short-term impact of the implemented change ideas. Overall, four change ideas were identified and tested, each lasting one week. Three outcome indicators were employed to test for change in practice i.e. preoperative bath recommendation, baths taken and completion of recommended baths. Data were analysed using STATA 14.2, and presented using tables, bar graphs and run charts. Results At the baseline phase of the study only 44.44% (n=27) of women had been recommended by nurses to bath prior to their C-section. Of the women recommended to bath at the pre-operative stage, only 41.66% (i.e., n= 12) had bathed at least once and 25.00% (n = 12) had completed the number of recommended baths. All (100.00%) (n = 5) those who bathed once and/or completed recommended baths had used soap. By the intervention phase, 92.00% (n=23) of women had been recommended to perform preoperative bathing, 86.95% (n = 20) bathed at least once, and 73.91% (n =17) completed the number of recommended baths. Overall, by the endline phase, the proportion of women recommended to bath had increased from 44.44% to 85.18%. The proportion of women who bathed at least once increased from 41.66 % to 91.30% and the proportion of women who completed the number of recommended baths increased from 25.00% to 86.95%. Moreover, all women who bathed either once or completed baths recommended baths used soap. Conclusion By the endline phase, there was improvement in the three outcome indicators i.e., preoperative bath recommendation, baths taken and completion of recommended baths. Low awareness of iv preoperative bathing advantages was associated with reduced recommendation of the practice. Recommendations include further research to examine the effects of preoperative bathing on SSI incidence. Such epidemiological research could be used to promote pre-operative bathing in low resource settings.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Epidemiology (Implementation Science) to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2021